Intimate partner violence among HIV-infected pregnant women initiating antiretroviral therapy in South Africa - Bernstein, Molly (Department of Public Health and Family Medicine, 2015)
Background: Intimate Partner Violence (IPV) is recognized globally as a major public health concern linked to numerous adverse physical, mental, sexual and reproductive health outcomes. IPV is associated with both pregnancy and HIV-infection independently, but there are few data on IPV in populations of HIV-infected pregnant women. We examined the prevalence and predicators of IPV among pregnant women initiating lifelong antiretroviral therapy (ART) in a large primary care clinic in Cape Town, South Africa. Methods: Consecutive pregnant women seeking antenatal care in Gugulethu, Cape Town were recruited into the MCH-ART study examining service models for postpartum ART care. IPV, depression, alcohol and drug use, and emotional distress were assessed using the 13-item WHO Violence Against Women questionnaire, the Edinburgh Postnatal Depression Scale (EPDS), alcohol and drug use disorders identification test (AUDIT/DUDIT) and the Kessler-10 (K-10) scale, respectively. Questionnaires were administered privately by trained interviewers. Women identified with specific IPV or mental health concerns were referred to appropriate services. Logistic regression was used to examine factors independently associated with experiences of IPV after adjusting for age and socioeconomic status. Results: From April 2013-May 2014, 623 women were enrolled (median age, 28 years):97% reported being in a relationship, 38% were married and/or cohabiting and 70% reported not having discussed or agreed on pregnancy intentions prior to conception . Overall, 21%(n=132) reported experiencing ≥ 1 act of IPV in the past 12 months, including emotional violence(15%), physical violence(15%) and sexual violence(2%). Of those reporting any IPV, 48% reported experiencing multiple types. Emotional and physical violence were most prevalent among women 18-24 years old, while sexual violence was most commonly reported among women 25-29 years old. Women who reported not discussing or disagreeing on pregnancy intentions with their partners prior to conception were significantly more likely to experience violence(p=0.030), and women who experienced IPV reported higher levels of substance abuse, depression and emotional distress(p<0.001 for all associations). Discussion: These data demonstrate high levels of IPV in this population. While the potential impact of HIV-infection, pregnancy and pregnancy intention on the risk of IPV and related factors require further research, IPV-related screening and support services should be considered as part of the package of care for ART in pregnancy.